A study on the efficacy of bee propolis as an antimicrobial agent against streptococcus mutans - De los Reyes, Jan Rael A.; Sulit, Jan Vincent Michael; Meneses, Michelle Marie Z. (Co-Author and Adviser).
Dental caries is the most common oral pathology affecting teeth. Throughout the years various treatments have been tried to combat this disease. Bee propolis or more commonly know as beeswax is currently one of the newer compounds being tested for its antimicrobial properties. This study hopes to test its antimicrobial properties and determine which concentration levels are effective against Streptococcus mutans. METHODS: The study made use of the disk diffusion method using different concentrations of bee propolis. The plates with inoculated Streptococcus mutans and bee propolis were incubated for 96 hours and then the zone of inhibition was measured. RESULTS: Mean data were recorded and subjected to one way ANOVA and Tukey HSD for statistical analysis. It was found that the 80% bee propolis solution was the most effective. Compared to 90% honey solution, it was also found that they have no significant difference in their antimicrobial properties. CONCLUSION: Bee propolis is an effective antimicrobial agent against streptococcus mutans.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.